Development of Education Management Competency Measurement Instruments with an Outcome-Based Education (OBE) - Fitri Nurmahmudah; Eka Cahya Sari Putra; Noorhapizah Noorhapizah; Fathul Jannah; Akhmad Riandy Agusta; Aliyah Rasyid Baswedan (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
This research aims to develop instruments used in measuring educational management competencies based on lecture outcomes. The method used is R&D with a quantitative approach. This research was conducted in Yogyakarta, Indonesia. The sample used was 715 students. Content validity was tested using the Aiken V index formula. Construct validity was tested using Confirmatory Factor Analysis (CFA). The results of this study indicate that the content validity coefficient is > 0.8, indicating that the statement items are valid. The KMO value (0.982) is > 0.05, indicating an adequate model fit. Scree Plot meets the unidimensional criterion, that is, it can be used to measure 1 dominant factor. Statistics X2 467, RMSEA 0.042, SRMR 0.030, CFI 0.990, NFI 0.989, meaning goodness of fit. The recommendation of this research is to use it to measure educational management competencies among educators worldwide, with diverse regional characteristics. So, in the long term, learning quality improves because it has a quality measurement tool. In practice, this instrument enables educators and institutions to evaluate and strengthen management skills, thereby improving the quality of learning and institutional performance. Academically, it advances research in educational measurement by providing a psychometrically sound instrument that supports broader implementation of OBE.